Predicting the risk of type 2 diabetes: Standardized diabetes risk score among the Khmer ethnic minority in Vietnam - Nguyen, Tuyen Thi Hong; Duong, Lam Phuc (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Predicting the risk of progression to type 2 diabetes, as well as identifying the factors that increase this risk, helps the population adjust the modifiable risk factors, improve quality of life, and reduce the disease burden. Subjects and methods. A cross-sectional study was conducted on 918 ethnic Khmer minority people aged 40 and above in Vietnam who had never been diagnosed with type 2 diabetes. Objective. To predict the 10-year risk of type 2 diabetes, the Finnish Diabetes Risk Scoring Scale, adjusted for the Asian population with modification of the waist circumpherence and Body Mass Index Cut-Offs, was used. Results. The 10-year predicted risk of progression to type 2 diabetes in ethnic Khmer people aged 40 years and older in southern Vietnam, using the Asian-modified Finnish Diabetes Risk Scoring Scale, resulted 10.54% in the total population study, females have a higher risk at 12.62% compared to 8.01% of males. Among the items that make up the Finnish Diabetes Risk Scoring Scale, age, waist circumference, BMI, family history of diabetes, history of high blood glucose, and use of blood pressure medication were the most accurate predictors, with the area under the Receiver operating characteristic (ROC) curve at 0.83, 0.81, 0.77, 0.75, 0.74 and 0.73 respectively. The optimal cut-off score to identify progression to tipe 2 diabetes was 13.5 points (Se = 1.00, Sp = 1.00, p < 0.001). The multivariable logistic regression model shows that factors associated with high risk of type 2 diabetes progression in 10 years are age, gender, occupation, economic status, education level and regular alcohol consumption (p < 0.05). The study results provide a basis for proposing potential solutions to reduce modifiable risk factors for type 2 diabetes in the population. These include providing culturally appropriate health education and changing behavior to address alcohol consumption. Discussion and conclusions. The use of the Asian-modified Finnish Diabetes Risk Scoring Scale to predict the risk of progression to type 2 diabetes and as a screening tool for undiagnosed type 2 diabetes is appropriate for the Vietnamese Khmer population.